The Connection Between Parity and the Incidence of Abortion in Reproductive Health Studies - Novita Matantu; Tut Rayani Aksohini Wijayanti; Reny Retnaningsih (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Abortion remains a significant reproductive health issue worldwide, with around 20 million cases recorded annually, leading to approximately 70,000 maternal deaths each year. In Southeast Asia, including Indonesia, approximately 4.2 million abortion cases occur annually. In Indonesia, spontaneous abortion accounts for 10-15% of all pregnancies, while induced (provoked) abortion is estimated to range from 750,000 to 1.5 million cases per year. Several factors can influence the incidence of abortion, one of which is parity the number of previous pregnancies a woman has carried to a viable gestational age. This study aims to analyze the relationship between parity and the incidence of abortion, contributing to a better understanding of how reproductive history impacts abortion rates. The research used an analytical design with a cross-sectional approach, involving a sample of 122 mothers selected through simple random sampling. The findings revealed that 45.9% of the mothers had safe parity, while 54.1% had unsafe parity. Regarding the type of abortion, 97.5% of respondents experienced spontaneous abortion, while 2.5% underwent induced abortion. Data analysis was conducted using the chi-square test at a significance level of 0.05, which produced a p-value of 0.562, indicating no significant relationship between parity and the incidence of abortion. These results suggest that parity is not a significant factor influencing abortion incidence in this sample. While other factors may contribute to abortion risk, further research is needed to explore additional variables that may play a role. This study underscores the complexity of abortion incidents and highlights the need for broader investigations to understand the diverse influences on reproductive health outcomes, beyond parity alone.